Reversible bone pain and symmetric bone scan uptake in a dialysis patient treated with cinacalcet: a case report - Lenz, Oliver (2010)
Introduction The medical management of secondary hyperparathyroidism in patients with end-stage renal disease involves a combination of dietary restrictions, phosphate binders, active vitamin D analogs, and calcimimetics. Case presentation We report the case of a 36-year-old Hispanic dialysis patient, originally from Cuba and now residing in the USA, who developed severe bone pain and muscle twitching after starting low dose cinacalcet, despite normal pre-dialysis ionized calcium and elevated parathyroid hormone. The clinical symptoms correlated with increased symmetrical uptake on bone scan that resolved rapidly upon discontinuation of cinacalcet. Conclusion Cinacalcet may induce severe bone pain and a unique bone scan uptake pattern in hemodialysis patients.